THE IMPACT OF PHYSICAL ABUSE AND SEXUAL PREDATORS ON FOOD RIDER JOB STRESS: THE MODERATING OF SOCIAL SUPPORT TO EMPLOYEE JOB STRESS - Nursyuhada Munirah Redzuan; Aslinda Mohd Shahril; Chemah Tamby Chik; Mohd Shazali Md Sharif, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
It is believed that customer rudeness is a widespread problem affecting food delivery employees since they have direct contact with customers and have to deal with the situation. Therefore, this study aimed to examine the impact of physical abuse and sexual predators on food rider job stress, the moderating of social support, real-time feedback usage, and employee engagement. A quantitative study was conducted with 263 respondents consisting of employees who had experience dealing with physical abuse and sexual predators in Klang Valley, Malaysia. SPSS and AMOS were used for empirical analysis to investigate the relationship. The results show that physical abuse and sexual predators were negatively related to employees’ job stress and confirm that social support moderates the relationship between physical abuse and job stress. In addition, social support also moderates the relationship between physical abuse and employees’ job stress. In addition, social support also moderates the relationship between sexual predators and employees’ job stress. The study succeeded in supporting the relationship between employee job stress and real-time employee feedback. In addition, the results suggest positive support for the relationship between real-time feedback and employee engagement. This study contributes to the Conservation of Resources theory on how social support can reduce employee job stress.